ШЛЯХИ ЗАПОБІГАННЯ ПОРУШЕННЯМ ПРИНЦИПІВ НАУКОВОЇ ТА АКАДЕМІЧНОЇ ЕТИКИ СТУДЕНТАМИ ВНЗ - Черновол-Ткаченко, О.А. (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 1970)
Стаття є спробою розробити низку практичних рекомендацій із запобігання порушенням принципів наукової та академічної етики студентами ВНЗ на сучасному етапі. Наголошується необхідність системності та раціональності у побудові засад етичної поведінки. Стаття також акцентує поняття особистої відповідальності студентів за якість їх власної освіти.Ключові слова: відповідальність, норми етичної поведінки, принципи наукової та академічної етики, самостійність. Черновол-Ткаченко О.А. Пути предотвращения нарушений принципов научной и академической этики студентами вузов. Статья является попыткой разработать ряд практических рекомендаций по предотвращению нарушений принципов научной и академической этики студентами вузов на современном этапе. Подчеркивается необходимость системности и рациональности в построении основ этичного поведения. Статья также рассматривает понятие личной ответственности студентов за качество их собственного образования.Ключевые слова: нормы этичного поведения, ответственность, принципы научной и академической этики, самостоятельность. Chornovol-Tkachenko O.O. Ways to prevent breaking principles of scientific and academic ethics by university students. The paper attempts at developing a set of practical guidelines on prevention of violating principles of scientific and academic ethics by university students at present. It accentuates relevance of a systemic and rational approach in creating the background for ethical behavior. The paper also analyses the notion of students’ personal responsibility for the quality of their education.Key words: norms of ethic behavior, principles of scientific and academic ethics, responsibility, self-reliance.